Λ-Statistical Convergence in Paranormed Space. (10th December 2013) - Alghamdi, Mohammed A.; Mursaleen, Mohammad
Abstract : The concept of λ -statistical convergence for sequences of real numbers was introduced in Mursaleen (2000). In this paper, we prove decomposition theorem for λ -statistical convergence. We also define and study λ -statistical convergence, λ -statistically Cauchy, and strongly λ p -summability in Paranormed Space.